Historical Cost dan General Price Level Accounting: Analisis Relevansi Indikator Keuangan - Meythi -; Sheffie Teresa (Universitas Kristen Maranatha, 2012)
In conventional accounting, financial statements are based on the historical cost principle that assumes that prices (monetary unit) are stable. Conventional accounting recognizes neither changes in the general price level nor changes in the specific price level. Consequently, if there are any changes in purchasing power such as in inflation period, the historical financial statement are not economically relevant and also income is usually overstated, and the fixed assets are usually understated. General Price Level Accounting will do restatement the components of financial statement to be a rupiah on a similar level of purchasing power, but without changes in accounting principles which using on conventional accounting. In this research did to PT Hanjaya Mandala Sampoerna Tbk. dan PT Kalbe Farma Tbk. are one of industrial sector it is not free of influence inflation condition. Also the result researches concerning the influence of applied general price level accounting on the financial statement will be compared as considerations whether the general price level adjustment is necessary needed. The hypothesis test did with based on t-test pair sample (wilcoxon). The result of research onï¡ = 5% showed that fifteen indicator tested there are twelve indicator showed significant different between financial report Historical Cost with financial report adjusted with General Price Level Accounting.